Hybrid piezo-, pyro-, and triboelectric nanogenerator based on PVDF and rGO composite fibers for a multifunctional approach to energy harvesting applications - Sunija Sukumaran; Piotr K. Szewczyk; Tomasz Bajda; Urszula Stachewicz (Materials & Design)
Recently, wearable nanogenerators have gained interest in energy harvesting and sensors, driven by smart electronics and Internet of Things (IoT) advancements. Here, we have developed a multifunctional nanogenerator that can convert mechanical and thermal energy into electrical energy via piezoelectric, triboelectric, and pyroelectric effects. The electrospun nanogenerator was fabricated to investigate the effect of reduced graphene oxide (rGO) on the energy generation of polyvinylidene fluoride (PVDF) fibers. The highest amount of electroactive β phase (81 %) and crystallinity (48.58 %) were obtained for 7 wt% rGO/PVDF fiber composite. Then, the 7 wt% rGO/PVDF composite was taken to prepare the piezo, tribo, and pyroelectric nanogenerator, and characterized using piezoresponse force microscopy (PFM), Kelvin probe microscopy (KPFM), and scanning thermal microscopy (SThM). Furthermore, the nanogenerator was made using the composite mat, illustrating its potential for powering small electronic devices using piezoelectric power and an enormous triboelectric power density of 3.37 ± 0.72 mWcm−2. We also demonstrate the device’s multifunctionality under thermal fluctuations. The results show the synergetic tribo and pyroelectric current of 33nA from 7 wt% rGO/PVDF. The present work indicates the significance of rGO inclusion into a PVDF matrix, resulting in enhanced multifunctional properties for energy harvesting, thereby enabling self-powering capabilities for microelectronic devices.